2014
DOI: 10.1186/1476-7120-12-44
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of cardiac output and pulmonary vascular resistance by contrast echocardiography transit time measurement: a prospective pilot study

Abstract: BackgroundStudies with other imaging modalities have demonstrated a relationship between contrast transit and cardiac output (CO) and pulmonary vascular resistance (PVR). We tested the hypothesis that the transit time during contrast echocardiography could accurately estimate both CO and PVR compared to right heart catheterization (RHC).Methods27 patients scheduled for RHC had 2D-echocardiogram immediately prior to RHC. 3 ml of DEFINITY contrast followed by a 10 ml saline flush was injected, and a multi-cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…CEUS‐derived PTT correlates well with true volumes in an in‐vitro setup, with PTT measured via MRI and with levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) . Choi et al . showed that cardiac output measured by right heart catheterization correlates with transit times measured with contrast echocardiography.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…CEUS‐derived PTT correlates well with true volumes in an in‐vitro setup, with PTT measured via MRI and with levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) . Choi et al . showed that cardiac output measured by right heart catheterization correlates with transit times measured with contrast echocardiography.…”
Section: Introductionmentioning
confidence: 93%
“…14,15 CEUS-derived PTT correlates well with true volumes in an in-vitro setup, 16 with PTT measured via MRI and with levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP). 1 Choi et al 17 showed that cardiac output measured by right heart catheterization correlates with transit times measured with contrast echocardiography. This was shown earlier already by Sherman et al, 18 assessing intracardiac hemodynamics using CEUS validated against right heart catheterization and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the Opotowsky method had a superior receiver-operating characteristic curve for discrimination of PVR >3 Wood units compared with the Abbas method. 41 Finally, Choi et al 42 showed that Definity dye transit time from peak opacification of right ventricle to first appearance in the left ventricle could be used to estimate PVR and cardiac output. In that study, the transit time for the contrast to travel from the right ventricle to the left ventricle was directly proportional to PVR and inversely proportional to cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the transit time for the contrast to travel from the right ventricle to the left ventricle was directly proportional to PVR and inversely proportional to cardiac output. Importantly, the transit time described by Choi et al 42 is a measure of blood flow, whereas pPTT is a surrogate measure of pressure pulse wave velocity. Consistent with this, and unlike the dye transit time, pPTT was inversely proportional to PVR and directly proportional to right ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…No final do século XX e nas primeiras décadas do século XXI, observam-se publicações de novos trabalhos investigando os tempos de trânsito circulatórios, desta vez avaliados por meio de métodos de imagem modernos, notadamente ressonância magnética, tomografia computadorizada e ultrassonografia (13,15,22,23,(28)(29)(30). Além do valor diagnóstico associado à avaliação dos TTC, o estudo da dinâmica do meio de contraste permite prever de forma mais consistente os tempos de aquisição de imagens (16,17,19,20,29).…”
Section: Discussionunclassified